Ethnobotany and ethnopharmacology of Tabernaemontana divaricata - Pratchayasakul W. (2014)
Tabernaemontana divaricata a common garden plant in tropical countries has been used as a traditional medicine. However, no recent review articles of T. divaricata, particularly discussing its pharmacological properties, are available. This review presents the ethnobotany and ethnopharmacology of T. divaricata as well as its potential therapeutic benefits especially of the alkaloidal and non-alkaloidal constituents. Included, are the characteristics of 66 alkaloids isolated and identified from T. divaricata. Non-alkaloids including the enzymes, pyrolytic oil, hydrocarbons, terpenoid and phenolic acids are also documented. Chemotaxonomic aspects of each alkaloid as well as information regarding the pharmacology of crude extracts and individual alkaloids from T. divaricata have been assembled and appraised. The beneficial properties of T. divaricata are antioxidant, anti-infection, anti-tumour action, analgesia and the enhancement of cholinergic activity in both peripheral and central nervous systems. The augmentation of cholinergic function may be of therapeutic benefit for many neurodegenerative diseases, particularly myasthenia gravis and Alzheimer's disease.